The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/jb.06112-11
|View full text |Cite
|
Sign up to set email alerts
|

Lag Phase Is a Distinct Growth Phase That Prepares Bacteria for Exponential Growth and Involves Transient Metal Accumulation

Abstract: Lag phase represents the earliest and most poorly understood stage of the bacterial growth cycle. We developed a reproducible experimental system and conducted functional genomic and physiological analyses of a 2-h lag phase in Salmonella enterica serovar Typhimurium. Adaptation began within 4 min of inoculation into fresh LB medium with the transient expression of genes involved in phosphate uptake. The main lag-phase transcriptional program initiated at 20 min with the upregulation of 945 genes encoding proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
380
1
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(443 citation statements)
references
References 115 publications
(112 reference statements)
19
380
1
16
Order By: Relevance
“…In the case of untreated cells, the bacterial replication goes to stationary phase after 7 h of incubation. During the lag phase, cellular metabolism is accelerated, resulting in rapid biosynthesis of cellular macromolecules, primarily enzymes (Rolfe et al, 2012). In this study on the treatment with ZnO Nps, cells showed moderate increase in size, thereby limiting cellular metabolism and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of untreated cells, the bacterial replication goes to stationary phase after 7 h of incubation. During the lag phase, cellular metabolism is accelerated, resulting in rapid biosynthesis of cellular macromolecules, primarily enzymes (Rolfe et al, 2012). In this study on the treatment with ZnO Nps, cells showed moderate increase in size, thereby limiting cellular metabolism and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to identify comprehensive gene networks modulated by SprC. Bacterial growth is most active in logarithmic phase that is involved with DNA synthesis, coupling with transcription and translation and synthesizing indispensable biological macromolecules [23]. In the present study, we chose the late exponential growth phase bacteria (cultured for 6 h) for analysis of proteomics, because SprC reached the maximum amount at this period compared with early and middle exponential growth phases (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows the lag time for both strains. Lag time is the initial period in the life of a bacterial population when cells are adjusting to a new environment before starting exponential growth (Rolfe et al 2012). Interestingly, only very minor differences in lag time were observed for C8 and C10 up to 5 mM MCFAs for both strains.…”
Section: Effect Of Mcfas On Bacterial Growthmentioning
confidence: 98%